2008
DOI: 10.1086/589456
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific Associations between Circulating Antioxidant Levels and Life‐History Variation in Birds

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
117
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(128 citation statements)
references
References 100 publications
(88 reference statements)
8
117
2
1
Order By: Relevance
“…At least in birds, it has recently been shown that the antioxidant capacity has a complex pattern relative to longevity (Cohen et al, 2008), whereby higher antioxidant levels were generally characteristic of 'fast-paced' life-history traits such as rapid development, low survival, smaller body size, larger clutch size and higher massspecific metabolic rate. Thus, convincing a priori predictions about how cells of tropical and temperate birds might resist oxidative and non-oxidative stress are difficult to make.…”
Section: Discussionmentioning
confidence: 99%
“…At least in birds, it has recently been shown that the antioxidant capacity has a complex pattern relative to longevity (Cohen et al, 2008), whereby higher antioxidant levels were generally characteristic of 'fast-paced' life-history traits such as rapid development, low survival, smaller body size, larger clutch size and higher massspecific metabolic rate. Thus, convincing a priori predictions about how cells of tropical and temperate birds might resist oxidative and non-oxidative stress are difficult to make.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the parallel increase of uric acid levels is not well supported by human studies, which report decreases, increases, or no change with age . Although uric acid in blood may contribute to controlling oxidative stress (Ames et al 1981;Machin et al 2004;Costantini 2008; but see Cohen et al 2007Cohen et al , 2008, its role in avoiding lipid peroxidation could be minor because it is, in fact, a hydrosoluble compound . Moreover, uric acid levels in plasma can be influenced by the protein content in the diet Smith et al 2007) or by protein catabolism associated with starvation (e.g., Alonso-Alvarez and Ferrer 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the amount of RS produced during exercise may be different if measured in a bird as opposed to a non-flying mammal, and birds may be more susceptible to RS damage via lipid peroxidation of stored fats. Further information on the interspecific relationship between BMR, lifespan and RS production can be found in other thorough reviews (Barja, 2007;Brand et al, 2004;Cohen et al, 2008;Costantini et al, 2010b;Hulbert and Else, 2000;Hulbert et al, 2007;Jimenez et al, 2014;Munshi-South and Wilkinson, 2010;Perez-Campo et al, 1998;Selman et al, 2012). …”
Section: Among-species Differences In Bmrmentioning
confidence: 99%